A 25-Year Perspective on Logic Programming Achievements of the Italian Association for Logic Programming, GULP - Dovier, Agostino; Pontelli, Enrico; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book celebrates the 25th anniversary of GULP$1 (Bthe Italian Association for Logic Programming. Authored by Italian researchers at the leading edge of their fields, it presents a state-of-the-art survey of logic programming, making it a useful reference for both researchers and students. The volume contains 14 invited papers, each giving a detailed analysis of a specific field of logic programming and providing both a historical perspective and a precise discussion of current research. The book closes with a chapter reviewing in detail the main applications of logic programming developed in Italian researchers in the last 25 years, illustrating successful work done and potential directions for future developments.s
Twenty-Five Years of Logic Programming in Italy -- Logic Programming in Italy: A Historical Perspective -- Theoretical Foundations and Semantics of Logic Programming -- Theory-Specific Automated Reasoning -- Constraint Logic Programming -- Knowledge Representation and Non-monotonic Reasoning -- The Transformational Approach to Program Development -- Static Analysis, Abstract Interpretation and Verification in (Constraint Logic) Programming -- Answer Set Programming -- Logic Programming Languages for Databases and the Web -- Agents, Multi-Agent Systems and Declarative Programming: What, When, Where, Why, Who, How? -- Concurrent and Reactive Constraint Programming -- Proof-Theoretic and Higher-Order Extensions of Logic Programming -- Transformation and Debugging of Functional Logic Programs -- 25 Years of Applications of Logic Programming in Italy.
Keywords: Computer science; Information theory; Logic design; Artificial intelligence; Computer Science; Mathematical Logic and Formal Languages; Logics and Meanings of Programs; Programming Techniques; Mathematics of Computing; Theory of Computation; Artificial Intelligence (incl. Robotics).